Review of the concept of quality in Hass avocado and the pre-harvest and harvest factors that determine it under tropical conditions - Ramírez-Gil, Joaquín Guillermo; Franco, German; Henao-Rojas, Juan Camilo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Avocado is one of the most desirable fruits worldwide because of its flavor and nutritional contributions. Currently, Colombia is a very dynamic country where the cultivated area and volumes of exported fruits have been increasing year after year. This situation poses a challenge for the country, which must produce fruits with excellent parameters of ripening, external and internal quality. This study used a series of elements associated with quality in avocado and its application in tropical conditions, which were determined based on reports from the world scientific literature reported in journals, books, manuals and conferences. In addition, information obtained from commercial esays on plantations and the experiences of packing and marketing companies in Colombia was used. The approach presented here is associated with a modern concept of quality in the food industry and how it can be applied to the avocado value chain; preharvest aspects that determine quality, management practices conducive to improving quality, and harvest parameters and their relationship with quality were also used. This study generated alternatives for increasing the added value in the avocado production system based on quality parameters and identified delays in the supply chain of this important agro-industry under tropical conditions.